Performance and emission parameters of single cylinder diesel engine using castor oil bio-diesel blended fuels. Issue 1 (November 2015) - Rahimi, A; Ghobadian, B; Najafi, G; Jaliliantabar, F; Mamat, R
Abstract: The purpose of this study is to investigate the performance and emission parameters of a CI single cylinder diesel engine operating on biodiesel-diesel blends (B0, B5, B10, B15 and E20: 20% biodiesel and 80% diesel by volume). A reactor was designed, fabricated and evaluated for biodiesel production. The results showed that increasing the biodiesel content in the blend fuel will increase the performance parameters and decrease the emission parameters. Maximum power was detected for B0 at 2650 rpm and maximum torque was belonged to B20 at 1600 rpm. The experimental results revealed that using biodiesel-diesel blended fuels increased the power and torque output of the engine. For biodiesel blends it was found that the specific fuel consumption (sfc) was decreased. B10 had the minimum amount for sfc. The concentration of CO2 and HC emissions in the exhaust pipe were measured and found to be decreased when biodiesel blends were introduced. This was due to the high oxygen percentage in the biodiesel compared to the net diesel fuel. In contrast, the concentration of CO and NOx was found to be increased when biodiesel is introduced.